The Building of Character Nation Based on Islamic Religion Education in School - Aries Abbas; Marhamah Marhamah; Ahmad Rifa’i (Syntax Corporation Indonesia, 2021)
The character of a nation is a benchmark of the success of education in a nation and state. Because in essence the main purpose of education is to make humans mature. Meanwhile, Islam is a religion that emphasizes the importance of the formation of the character, because the Prophet Muhammad actually said I was sent to perfect morals. The purpose of this research is to find out about how to build the character of a nation based on Islamic education. Implementation of Islamic learning in schools in Jakarta. The focus of the application of Islamic religious education materials that can improve the character of the nation. The research methodology used is a descriptive qualitative research method using data sources from the literature review and field research directly to the school. Research finding that the quality of Islamic education that is integrated with all existing lessons will have an impact on the nation's character. National education is realized in creating people who have faith and are dedicated to God who is almighty, independent, honest, healthy, able to keep up with the times and be responsible.